Epidemiology and Relative Severity of Influenza Subtypes in Singapore in the Post-Pandemic Period from 2009 to 2010. (23rd September 2017) - Goh, Ee Hui; Jiang, Lili; Hsu, Jung Pu; Tan, Linda Wei Lin; Lim, Wei Yen; Phoon, Meng Chee; Leo, Yee Sin; Barr, Ian G; Chow, Vincent Tak Kwong; Lee, Vernon J; Lin, Cui; Lin, Raymond; et al.
Abstract : We assessed and found cross-protection between the influenza pandemic and 2 seasonal viruses that circulated in Singapore. Age-related differences in disease severity between the subtypes were investigated, and we demonstrate birth cohort effects consistent with the theory of antigenic sin. Abstract: Background: After 2009, pandemic influenza A(H1N1) [A(H1N1)pdm09] cocirculated with A(H3N2) and B in Singapore. Methods: A cohort of 760 participants contributed demographic data and up to 4 blood samples each from October 2009 to September 2010. We compared epidemiology of the 3 subtypes and investigated evidence for heterotypic immunity through multivariable logistic regression using a generalized estimating equation. To examine age-related differences in severity between subtypes, we used LOESS (locally weighted smoothing) plots of hospitalization to infection ratios and explored birth cohort effects referencing the pandemic years (1957; 1968). Results: Having more household members aged 5–19 years and frequent public transport use increased risk of infection, while preexisting antibodies against the same subtype (odds ratio [OR], 0.61; P = .002) and previous influenza infection against heterotypic infections (OR, 0.32; P = .045) were protective. A(H1N1)pdm09 severity peaked in those born around 1957, while A(H3N2) severity was least in the youngest individuals and increased until it surpassed A(H1N1)pdm09 in those born in 1952 or earlier. Further analysis showed that severity of A(H1N1)pdm09 was less than that for A(H3N2) in those born in 1956 or earlier ( P = .021) and vice versa for those born in 1968 or later ( P < .001), with no difference in those born between 1957 and 1967 ( P = .632). Conclusions: Our findings suggest that childhood exposures had long-term impact on immune responses consistent with the theory of antigenic sin. This, plus observations on short-term cross-protection, have implications for vaccination and influenza epidemic and pandemic mitigation strategies.